Percursos da formação do professor para uso da documentação pedagógica como registro histórico - Dias, Maria Júlia de Oliveira (2018)
We sought to investigate how the pedagogical coordinator can mobilize teachers to use pedagogical documentation in favor of children in Early Childhood Education. The main goal of the research was to develop a formative process in which teachers of children from birth to age 5 reflected on the use of the register in their teaching experiences and found ways to improve their practice. The theoretical foundation was based on the writings of Imbernón (2016) regarding the concept of continuing education and to discuss the concept of pedagogical documentation and records, the inspiration was in the works of Freinet (1920), Freire (1992) and Warschauer (1993, 2001). The foundation of the methodology was supported by authors such as Passos (2016), Fiorentini (2004) and Thiollent (2016), who discuss the concepts of collaborative groups and action research. The research is linked to the professional performance of the researcher as pedagogical coordinator and its participants are nine teachers working with children from birth to age 5 of a private school in the south of the city of São Paulo. The data were produced from the realization of three reflective meetings with the teachers, in which questions were discussed regarding the use of records and pedagogical documentation. The dynamics of the meetings involved joint debates, raising hypothesis, problem identification and proposals for strategies to seek alternatives and adjustments, based on classroom records and practice. The meetings were recorded and the material produced was shared with the teachers and submitted to the analysis by the researcher. The results indicated a movement towards the constitution of a collaborative group. The teachers emphasized the lessons learned from the contact with more experienced colleagues and with materials produced in other contexts, their reports expressed the importance of documenting and giving voice to the children, so that they became aware of their experiences, their achievements and challenges. Another aspect revealed by the teachers' statements was the reflection of the practice of observation and recording that does not end with the explanation of the facts, but is reconstituted from thinking and discussion to establishing relationships and connections